Ischemic Stroke as a Manifestation of Cholesterol Embolization Syndrome Following Percutaneous Coronary Intervention - Ghimire, B.; Kanal, K.; Bajracharya, A.; Koirala, M. (Kathmandu University Medical Journal, 2021)
Cholesterol embolization syndrome (CES) is one of the major, yet underdiagnosed cause of morbidity and mortality following invasive coronary interventions. The major risk factors are elderly, male, atherosclerotic disease, anticoagulation and femoral access route. This multisystem disease affects skin, kidney, brain, eye and gastrointestinal tract. Only few cases of cholesterol embolization syndrome manifesting as an ischemic stroke are reported. We present a case of an elderly man, admitted to our ICU after percutaneous coronary intervention (PCI) who developed neurological deficits along with skin changes and renal failure. cholesterol embolization syndrome was suspected based upon the presence of cardiovascular risk factors, invasive cardiovascular intervention and clinical signs. The diagnosis of ischemic stroke made through plain MRI brain, revealed multiple areas of lacunar infarcts. He was treated with intermittent hemodialysis, statins and anti-platelet agents. On follow up, skin lesions and renal functions were improved; but slurring of speech and paresis persisted.